Optimalisasi Potensi BUMDes "Bina Usaha" Melalui Penerapan Teknologi dan Manajemen Pemasaran Produk di Desa Cinangka - Asep Rahmatullah; Dedy Khaerudin; Romli, Ombi; Mardiyah, Husna Febriani; Ramadhan, Muhammad Ghifari (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Empowering BUMDes for Business Development in Cinangka Village, Cinangka District, Serang Regency, Banten Province has much potential, particularly in the home industry, for processing melinjo fruit into products like Emping. However, partners face several issues in their business, including (1) production processes that are still conventional; (2) The lack of knowledge and management skills of BUMDes "Business Development" managers towards optimizing community economic empowerment; (3) The sales method is still manual, namely by leaving it at the nearest food stall, so it is still tricky for sales volume to reach the maximum target; (4) Not yet registered and has a trademark with the Directorate General of KI, Ministry of Law & Human Rights. Therefore, this Community Service aims to provide training and assist partners in managing BUMDes "Business Development" from the production process of making products to product sales methods to increase partners' sales results so that the local community's economy improves. This community service uses a participatory method, with the Cinangka Village "Business Development" group as the training target. The series of activities will be carried out in four stages: stage 1, analysis of the situation and conditions of partners; stage 2, preparation and technology transfer; stage 3, training and mentoring; stage 4, evaluation and program sustainability. The implementation of activities resulted in an overall increase of 85.28%, beginning with the production process, knowledge, and management skills for managing BUMDes' "Business Development" and product sales.